(untitled) (Rivista italiana di Paleontologia e Stratigrafia, 1992)
Within the "Calcare di Bari" Formation (Valanginian p.p.-Cenomanian) the Aptian is characterized by three lithostratigraphic members: the Palorbitoline limestone Member and the Corato limestone Member, mainly early Aptian in age (Bedoulian); the Bisceglie limestone Member mainly corresponding to almost the whole Upper Aptian (Gargasian- Clansayesian) yielding microfaunas of early Gargasian and later Gargasian to Clansayesian age. The Bedoulian is marked by a rich and diverse micropaleontological (Algae, Foraminifera) as well as macropaleontological (Rudists) communities, which include several age diagnostic species. A decreases in taxonomic diversity is observed close to the Bedoulian-Gargasian transition. It is related to paleoenvironmental changes, i.e. increasing restriction and/or emersions. The uppermost Aptian is marked by a new phase of normal marine conditions. Nevertheless no Rudist communities have been recorded. These paleoenvironmental changes are coeval with those known from the Southern Apennine successions which contain similar micropaleontological assemblages, especially during the Late Aptian.